Employment law essentials : your A to Z guide to HR compliance (J.J. Keller & Associates, Inc NeenahUS, 2013)
Presents topics which covers a specific area of compliance or best practices in employment law in the US. Describes who is covered by the law (where an underlying law applies) and provides a summary of the requirements or best practices, and information on state laws. Explains how laws and and regulations are referenced.
Keywords: EMPLOYMENT